Insights from the South Sector at Histria. New archaeological and anthropological data - Crețu, C.; Dabîca, M.; Soficaru, A. (Materiale și Cercetări Arheologice)
: Excavations conducted from 2012 to 2021 at the South Sector uncovered 34 graves, adding valuable new information to the mortuary record of the extramural cemetery of the settlement during the Late Roman and Early Byzantine periods (4th to 6th centuries AD). In addition to presenting and discussing the graves with their specific attributes such as the arrangement of diverse funerary structures, as well as body orientation and positioning, the skeletal remains were subjected to anthropological analysis for the first time to estimate the sex and age at death of the individuals and assess their health status while recording the documented pathological conditions. By constructing some individual profiles, we sought to briefly focus on detailing the challenges faced by individuals with particular and to offer insights into their lived experiences and difficulties when faced with such diseases. The diversity of funerary practices was evident, including reburials and cenotaphs. The high prevalence of graves with double sloped roof made of tiles in the South Sector contrasts markedly with the lower occurrence observed in the Basilica extra muros Sector, suggesting the possibility of a clustered group in the area of the former. By mapping graves based on chronological, sex, and age categories a comprehensive mortuary dossier is provided for the first time, integrating both older findings and these recent discoveries